Dentistry scientometric analysis: A comparative study between Brazil and other most productive countries in the area - Grácio, Maria Cláudia Cabrini [UNESP]; Oliveira, Ely Francina Tannuri de [UNESP]; Gurgel, Júlio de Araújo [UNESP]; Escalona, Maria Isabel; Guerrero, Antonio Pulgarin (Springer Nature, 2013)
This research aims at performing a comparative study between the Brazilian scientific production in Dentistry, from 2000 to 2009 and countries that contribute with at least 2 % of the world's scientific production indexed in the Scopus database. More specifically, we intend to assess the annual Brazilian scientific production by comparing it to the other countries', analyze the Brazilian and other countries' publications in journals with higher impact factors, as well as to highlight the scientific production from these countries and its international visibility, measured by its total and by its average of citations and normalized citation index per year, by comparing the countries, and to compare the index h of such countries. As work procedure, the SCImago Journal and Country Rank was used as source, identifying the group of producing countries in the Dentistry area from 1996 to 2009. From a total of 136 countries, 13 were highlighted as the most productive, each one of them accounting for at least 2 % the worldwide scientific production in the area. The following indicators were raised for each country: number of produced documents, total of citations, self-citations, average of citations per document and index h. We verified that Brazil is the only country in Latin America that is pictured among the most productive ones in the Dentistry area. We observed that Brazil presents a growing visibility and impact in the international scenery, what suggests that its production is constantly consolidating, with Brazilian scientific recognition in the main vehicles of dissemination in the area. © 2012 Akadémiai Kiadó, Budapest, Hungary.
Keywords: Dentistry scientific production; Index h; Information science research; Scientometric indicators